Determinants of Childhood Diarrhea in Households with Improved Water, Sanitation, and Hygiene (WASH) in Ethiopia: Evidence from a Repeated Cross-Sectional Study - Biniyam Sahiledengle; Kingsley Agho (SAGE Publishing, 2021)
Background: Determinants of childhood diarrhea in households with improved WASH (ie, households with improved drinking water sources, improved sanitation facilities, and those who practiced safe child stool disposal) are limited. This study aimed to identify the determinants of diarrhea among under-five children exclusively in households with improved Water, Sanitation, and Hygiene (WASH). Methods: A repeated cross-sectional study design was followed, and data from the Demographic and Health Survey (DHS) conducted between 2005 and 2016 in Ethiopia was used. A total of 1,975 child-mother pairs (257 children with diarrhea and 1718 children without diarrhea) in households with improved WASH were included in this study. Hierarchical conditional logistic regression models were used. Adjusted odds ratios (AOR) with corresponding 95% confidence intervals (CI) were estimated to determine the strength of association. Results: Children aged 13 to 24 months (Adjusted Odds Ratio [AOR] = 2.70, 95%CI: 1.69-4.32), children who did not receive the measles vaccine (AOR = 2.33, 95%CI: 1.60-3.39), and those residing in the agrarian region (AOR = 1.66, 95%CI: 1.10-2.49) were significantly more likely to develop diarrheal morbidity. The size of the child at birth was also found to be significantly associated with diarrheal morbidity. Conclusion: In this study, child factors (age of the child, vaccinated for measles, and the size of a child at birth), and household-related factors (contextual region) had a significant effect on the risk of childhood diarrheal morbidity in households with improved WASH in Ethiopia.